Workshop Pembelajaran PJOK Berorientasi HOTS Dan TGFU Bagi Guru PJOK Sekecamatan Karang Pucung - Dian Imam Saefulah; Kusmiyati Kusmiyati; Untung Nugroho (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
The implementation of HOTS (Higher Order Thinking Skill) based PJOK learning for PJOK teachers in the Karangpucung sub-district needs to be studied to improve the quality of PJOK learning. Therefore, this research aims to find out how to implement HOTS (Higher Order Thinking Skill) based on PJOK learning. Through this research activity, it is hoped that it will contribute to fellow PJOK teachers. This research is qualitative research with data instruments using observation, interviews, and documentation. The research was conducted for PJOK teachers in the Karangpucung sub-district. Data were analyzed using data triangulation. Data sources include school principals, fellow teachers, and FGD activities. Based on the research results, it is known that it is necessary to increase understanding regarding HOTS. Apart from that, PJOK teachers have implemented HOTS learning starting from planning, implementation, assessment, and evaluation. The research concludes that the implementation of HOTS-based PJOK learning for PJOK teachers in the Karangpucung sub-district has been implemented. This can be seen when PJOK teachers carry out planning, implementation, assessment, and evaluation of learning and have implemented HOTS